Application of EEG Signals – A Case Study - Guruprasad S.; Veena N.; S. Mahalakshmi (Advanced Aspects of Engineering Research Vol. 11, 2021)
Man-Machine-Interface (MMI) is a communication system between the brain and the computer to obtain and investigates the brain signals. The EEG captures the electrical signals produced by the nerve cells. The purpose of this paper is to report the results related to classification of EEG signals and based on the emotion playing an appropriate music to indicate the emotion of different people. The testing has been done on the dataset subjected to 10 subjects associated with hearing music chosen from patriotic, happy, romantic and sad songs along with relaxation activity.